Evaluation and injury investigation of a finite element foot and ankle model for small female occupants. Issue 5 (3rd September 2019) - Nie, Bingbing; Giudice, J. Sebastian; Poulard, David; Wu, Taotao; Panzer, Matthew B.
Abstract: Female occupants sustain high frequency of injury to the foot and ankle in motor vehicle crashes (MVCs). To investigate injury mechanisms, this study evaluated a finite element model of the foot and ankle of a small female occupant (F05). The model was validated in four loading conditions relevant to MVCs (axial rotation, dynamic inversion and eversion, dorsiflexion and axial impact) and scaling approaches were applied to available post-mortem human surrogate data to provide appropriate boundary conditions and experimental biofidelity targets. Compared to an average male model, the F05 model predicted more bony fractures in comparable dynamic loading conditions, consistent with field observations for female occupants in crash incidents. Further research is needed to improve model biofidelity and account for gender and age variations for female occupants. This model will be useful for understanding female-specific injury mechanisms and guiding the development of effective countermeasures in vehicle design.